The Employee Absenteeism Costs of Rheumatoid Arthritis. Issue 6 (June 2015) - Gunnarsson, Candace; Chen, Jie; Rizzo, John A.; Ladapo, Joseph A.; Naim, Ahmad; Lofland, Jennifer H.
<x xml:space="preserve">Abstract</x> Objective: To estimate indirect costs associated with rheumatoid arthritis (RA). Methods: This was a retrospective study using 1996–2006 US Medical Expenditure Panel Survey data. Employed individuals were aged 18 to 65 years. A two-part model estimated the probability of time lost from work and annual number of workdays missed due to illness. Results: Sixty-seven percent (209/312) of RA individuals missed work versus 58% (52, 046/89, 734) of those without RA (P = 0.0007). Among individuals who missed work, those with RA missed more workdays annually than those without RA ( <inline-graphic xlink:href="ark:/27927/pgjrpvjwd2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> = 13.659, 9.879, respectively; P = 0.008). Incremental per capita costs in annual lost workdays between those with and without RA were $596. Estimated national indirect costs of RA-related absenteeism were $252 million annually. Conclusions: Individuals with RA have higher probabilities of missing work and missing workdays than those without RA.